Imagining Bosnian Muslims in Central Europe : representations, transfers and exchanges - Šístek, František (Austrian and Habsburg studies, 2021)
"As a Slavic-speaking religious and ethnic "Other" living just a stone's throw from the symbolic heart of the continent, the Muslims of Bosnia and Herzegovina have long occupied a liminal space in the European imagination. To a significant degree, the wider representations and perceptions of this population can be traced to the reports of Central European-and especially Habsburg-diplomats, scholars, journalists, tourists, and other observers in the late nineteenth and early twentieth centuries. This volume assembles contributions from historians, anthropologists, political scientists, and literary scholars to examine the political, social, and discursive dimensions of Bosnian Muslims' encounters with the West since the nineteenth century"--